Web Document Summarisation: A Task-Oriented Evaluation - White, Ryen W.; Ruthven, Ian; Jose, Joemon M. (1st International Workshop on Digital Libraries (DLib 2001, part of DEXA 2001) Munich, Germany, 2001)
In this paper we present a query-biased summarization interface for web searching. The summarisation system has been specifically developed to act as a component in existing web search interfaces. The summaries allow the user to more effectively assess the content of web pages. We also present an experimental investigation of this approach. Our experimental results shows the system appears to be more useful and effective in helping users gauge document relevance than the traditional ranked titles/abstracts approach.